THE EFFICACY OF PROTECTIVE MEASURES IN CASES OF DOMESTIC VIOLENCE (CIPEEX, 2026)
Domestic violence constitutes one of the most serious social and legal problems in Brazil, affecting thousands of women in different family contexts. This study aims to analyze the effectiveness of protective measures provided for in the Maria da Penha Law, identifying their progress, challenges, and contribution to victim safety. The research was conducted using qualitative and quantitative methods, with a deductive approach, bibliographical, documentary, and historiographical analysis. The results indicate that, although protective measures represent a significant advance in victim protection, obstacles remain in their implementation, such as the lack of infrastructure in the judicial and police systems, the lack of effective monitoring, and cultural resistance that minimizes the severity of gender-based violence. It was found that the use of technological tools, such as electronic monitoring and the panic button, increases the effectiveness of these measures, as does the creation of specialized programs, such as the Maria da Penha Patrol. It is concluded that protective measures are effective, but they need to be strengthened through public policies, preventive actions, psychosocial support, and re-education programs for aggressors, so that they can fully fulfill their role of reducing domestic violence and promoting greater gender equality in Brazil.
Keywords: Domestic violence; Maria da Penha Law; Protective measures; Gender